The pathophysiology of cognitive impairment in individuals with heart failure: a systematic review - Ni, Reine Sam Shi; Mohamed Raffi, Hanis Qarissa; Dong, Yanhong (Frontiers in Cardiovascular Medicine, 2023)
Introduction Heart Failure and Cognitive Impairment are both on the rise and shown to be interlinked. Despite existing reviews delineating a relationship between heart failure and cognitive impairment, the underlying pathophysiology is not researched in great depth. Current literature proposed varying pathophysiological mechanisms and focused heavily on the prevalence of cognitive impairment and treatment interventions such as cardiac rehabilitation. In view of the limitations of previous reviews, this systematic review summarized the best existing evidence concerning different pathophysiological mechanisms behind cognitive impairment in individuals with heart failure. Methods Eight electronic databases including PubMed, Cochrane Library and EMBASE etc., two grey literatures (ProQuest Theses and Dissertations and Mednar) and hand-searching of references were performed using specific criteria regarding population, exposures and outcomes, before duplicate removal and screening using Endnote and Rayyan respectively. JBI critical appraisal tools for non-randomized studies were used for appraisal. Data extraction was performed using two modified forms from JBI Manual for Evidence Synthesis. Results Narrative synthesis was performed to summarize the data from 32 studies. There were three main themes—cognitive impairment due to changes in the brain: brain atrophy, alterations in grey matter and white matter, cerebral alterations, pathway or axis changes, neuroinflammation and hippocampal gene changes; cognitive impairment due to changes in the heart or systemic circulation: inflammation, oxidative stress and changes in serum biomarkers or proteins and the riser rhythm; cognitive impairment due to changes in both the brain and the heart, with seven studies obtaining negative results. There are some limitations such as having non-human studies and large numbers of cross-sectional studies etc. Discussion Considering the findings, future research should examine the bi-directional relationship between the brain and the heart as most of the existing research is about the effect of the heart on the brain. By understanding the different pathophysiological mechanisms, the management and prognosis of heart failure patients will be ameliorated. Interventions that slow down or even reverse cognitive impairment can be explored so that these two common issues will not add to the already aggravating disease burden. Systematic Review Registration This review is registered under PROSPERO. Identifier: CRD42022381359.